2022
DOI: 10.3390/su14020642
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Land Use/Land Cover Alteration on Climate Variability: An Analysis in the Aurangabad District of Maharashtra State, India

Abstract: Examining the influence of land use/land cover transformation on meteorological variables has become imperative for maintaining long-term climate sustainability. Rapid growth and haphazard expansion have caused the conversion of prime agricultural land into a built-up area. This study used multitemporal Landsat data to analyze land use/land cover (LULC) changes, and Terra Climate monthly data to examine the impact of land transformation on precipitation, minimum and maximum temperature, wind speed, and soil mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…From results it is observed that RF outperforms SVM in LC applications due to its robustness to outliers and noise also as compared to RF SVM is more sensitive to hyperparameters [38]. Obtained results show that the presented approach achieves improvement of 3% in overall accuracy for land cover classification compared to obtained in [28] since SAR sensors can acquire an image in all weather conditions in addition to these different combinations of polarization provides important LC details of the earth's surface which improves LC classification accuracy.…”
Section: Vv[db] Vv[db]mentioning
confidence: 98%
See 2 more Smart Citations
“…From results it is observed that RF outperforms SVM in LC applications due to its robustness to outliers and noise also as compared to RF SVM is more sensitive to hyperparameters [38]. Obtained results show that the presented approach achieves improvement of 3% in overall accuracy for land cover classification compared to obtained in [28] since SAR sensors can acquire an image in all weather conditions in addition to these different combinations of polarization provides important LC details of the earth's surface which improves LC classification accuracy.…”
Section: Vv[db] Vv[db]mentioning
confidence: 98%
“…Researchers are utilizing GEE in recent years for LC classification. The use of GEE for land cover classification using Landsat8 [24,25,27,28], sentinel2 [29] and combinations of sentinel2 and landsat8 [30] has shown good results. Therefore GEE presents great opportunities in dealing with remote sensing data for LC mapping in Pusad.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, LULCC in the tropics increase nitrate, phosphorus (PO 4 -), ammonium (NH 4 + ), electrical conductivity in bodies of water (including Na +, Mg 2+ , Cl Changes in land use/cover also have an impact on water resources through their contribution to processes like the introduction of invasive fauna and flora species into water and siltation [17,18]. Land uses such as agriculture and built up areas have been shown to influence soil moisture and climatic processes such as temperature and precipitation [19]. Water resources are often at the Centre of urban development but, as the city expands, the environmental pressure on its water resources increases [20].…”
Section: Setting the Contextmentioning
confidence: 99%
“…Land uses such as agriculture and built up areas have been shown to influence soil moisture and climatic processes such as temperatures and precipitation. The intensity of the precipitation can be reduced as result of the developmental activities whilst the temperatures increase with increased impervious surfaces [ 27 ]. One major problem is that most developing nations lack the resources necessary for efficient urban planning.…”
Section: Introductionmentioning
confidence: 99%